Dirasah Muqaranah al-Madhahib ‘an Ahkam al-Nikah - Sofyan, Abdullah Muhammad (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2021)
This is a brief study of some of the provisions relating to marriage. Marriage is the only legitimate means of reproduction and reproduction. Islam has been keen on the permanence and stability of this legitimate relationship and, therefore, prescribed the khutbah before the contract, as it is how the two parties get to know their respective life partners in terms of morals, natures and forms. The jurists may consider the fiancé to the fiancée to the extent permitted by Sharia. He has a repetition of consideration so that they are sure of their matter, either to end with the desired result of the sermon, which is marriage or to amend the sermon and annul it. If the sermon ends with what is desired from marriage, the jurists agree that the formula, the offer and acceptance, is a pillar of marriage. They differed in what is only the formula, such as the mandate. For example, some of the pillars and others counted it from others. They also agreed that the dowry is not a pillar or a condition but a duty to pay. A woman is a gift decided by God Almighty as her dignity. There is no limit for more, except that it is enacted to leave exaggeration in it and no limit to at least according to the Shafi'is and Hanbalis. Guardianship in marriage is a pillar for the public, except for the Ahnaf. The mandate is of two types: compulsory and choice mandates. Holding a feast is a Sunnah for those who can do it in the audience, and it is obligatory for some Malikis and Shafi'is. Keywords: Marriage, the four schools of thought, jurisprudence. الملخص: إن هذه دراسة موجزة في بعض الأحكام المتعلقة بالنكاح. فالنكاح هو الوسيلة الوحيدة المشروعة للتوالد والتكاثر. وقد حرص الإسلام على ديمومة هذه العلاقة المشروعة واستقرارها، ولذا شرع الخطبة قبل العقد، فهي الوسيلة التي يتعرف بها الطرفان كل على شريك حياته، من ناحية الأخلاق والطبائع والأشكال. وجوز الفقهاء نظر الخاطب إلى المخطوبة، بالقدر الذي أباحه الشرع. وله تكرير النظر ولها أيضا كذلك، حتى يكونا على يقين من أمرهما، فإما أن تنتهي بالنتيجة المرجوة من الخطبة وهي النكاح وإما أن يعدل عن الخطبة فيفسخها، وإذا ما انتهت الخطبة بما يرجى منها وهي النكاح، فالفقهاء متفقون على أن الصيغة وهي الإيجاب والقبول ركن من أركان النكاح، واختلفوا فيما سوى الصيغة كالولاية مثلا فعدها البعض من الأركان وعدها البعض الأخر من غيرها، واتفقوا كذلك في أن المهر ليس بركن ولا بشرط، وهو واجب تدفع للمرأة عطية قررها الله سبحانه كرامة لها، ولا حد لأكثر إلا أنه يسن ترك المغالاة فيه وكذلك لا حد لأقله عند الشافعية والحنابلة. والولاية في النكاح ركن عند الجمهور سوى الأحناف. والولاية نوعان ولاية إجبار وولاية اختيار. وإقامة الوليمة سنة للقادر عليها عند الجمهور، وواجبة عند بعض المالكية والشافعية. كلمات مفتاحية: النكاح، المذاهب الأربعة، الفقه.